THE ACUTE EFFECT OF WHOLE BODY VIBRATION TRAINING ON FLEXIBILITY AND EXPLOSIVE STRENGTH OF YOUNG GYMNASTS - G. Dallas; P. Kirialanis; V. Mellos (Termedia Publishing House, 2014)
The purpose of this study was to examine the acute effect of a single bout of whole body vibration (WBV) on flexibility and explosive strength of lower limbs in young artistic gymnasts. Thirty-two young competitive gymnasts volunteered to participate in this study, and were allocated to either the vibration group or traditional body weight training according to the vibration protocol. The vibration intervention consisted of a single bout of eccentric and concentric squatting movements on a vibration platform that was turned on (vibration group: VG n=15), whereas the traditional body weight (no vibration) group performed the same training protocol with the WBV device turned off (NVG: n= 17). Flexibility (sit and reach test) and explosive strength tests [squat jump (SJ), counter movement jump (CMJ), and single leg squat (right leg (RL) and left leg (LL))] were performed initially (pre-test), immediately after the intervention (post-test 1), and 15 minutes after the end of the intervention programme (post-test 15). Four 2x3 ANOVAs were used to examine the interaction between group (VG vs NVG) and time (pre, post 1, and post 15) with respect to examined variables. The results revealed that a significant interaction between group and time was found with respect to SJ (p 0.05). Further, the percentage improvement of the VG was significantly greater in all examined variables compared to the NVG. This study concluded that WBV training improves flexibility and explosive strength of lower limbs in young trained artistic gymnasts and maintains the initial level of performance for at least 15 minutes after the WBV intervention programme.